Dark tarot - Feehan, Christine (Feehan, Christine. Carpathian novel., 2022)
Sandu Berdardi continues to exist only to protect his people. An ancient Carpathian, his entire long life has been dedicated to honor above all else. He knows his time has passed, especially since he has not been able to find his lifemate--the anchor to keep him sane in a world he no longer understands. But just as he truly starts to give up hope, a voice reaches out to him in the night and his world explodes into color. Adalasia enters Sandu's mind seamlessly, as if she has been a part of him forever. While she can see the shape of things to come in her deck of cards, her gift is both a blessing and a curse. The true course of Sandu's quest remains unclear, with danger waiting at every turn. Adalasia cannot see everything the future holds, but she does know it is a journey they will take together. By joining him, she will start them down a dangerous, seductive path from which there is no turning back...